The Influence Of Intellectual Capital On Profitability With Moderate Sales Growth In Energy Sector Companies Listed On The Indonesia Stock Exchange (IDX) In 2019-2023 (International Journal of Environmental Sciences, 2025)
In an increasingly competitive business world, financial performance is one of the main indicators that investors pay attention to in assessing a company's prospects. One common measure of profitability used is return on assets (ROA), which reflects the rate of return based on the company's assets. In addition to physical and financial capital, intellectual capital also plays an important role in increasing the value of the company. Intellectual Capital, which consists of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA), has been widely studied in relation to company performance. This type of research is descriptive verification which aims to analyze the effect of VACA, VAHU, STVA on company performance as measured using ROA, and explore the role of company sales growth as a moderating variable. The research data used are 60 energy sector companies in 2019-2023 listed on the Indonesia Stock Exchange. The method used in this study is a quantitative approach with panel regression analysis and moderated regression analysis (MRA). The results of the study show that partially, VACA and VAHU have a significant positive effect on ROA, while STVA does not show a significant effect. Furthermore, the results of the moderation test show that sales growth (SGR) is able to strengthen the influence of VACA and STVA on ROA, but is not significant in moderating the relationship between VAHU and ROA. This finding indicates that the efficiency of physical capital use and human resource management are key factors in increasing the profitability of energy sector companies, and the role of structural capital becomes more effective when the company experiences growth. This study provides theoretical implications in the development of Intellectual Capital studies as well as managerial recommendations for companies to focus more on managing intellectual assets as strategic resources. In addition, the results of this study can be a consideration for investors in assessing the company's financial prospects through a more comprehensive non-financial approach